Status Kewarisan Anak Luar Kawin Dalam Perspektif Hukum Positif dan Hukum Islam Pasca Putusan MK Nomor 46/PUU-VII/2010 - Imadudin, Agung Nursufa (Jurnal EL-QANUNIY: Jurnal Ilmu-Ilmu Kesyariahan dan Pranata Sosial, 2024)
An illegitimate child will have legal consequences, namely having no legal relationship with his or her biological father, both regarding education and inheritance. Constitutional Court Decision Number 46/PUU-VII/2010, provides the position and rights of children outside of marriage, giving rise to dualism in its application. It is necessary to examine more deeply the status of inheritance rights of illegitimate children according to normative juridical and Islamic law, as well as what the status of inheritance rights of illegitimate children is after the Constitutional Court decision. In Islamic law and positive law, it is stated that illegitimate children cannot be assigned to their (biological) father. This means that illegitimate children cannot inherit from each other between the child and his father and his father's family based on the consensus of the ulama. The Constitutional Court's decision provides the right for illegitimate children to have a civil relationship with their father, as long as it can be proven based on science and technology and/or other legal evidence. In its implementation, this decision still requires an explanation in the form of legislation that regulates the extent of a child's civil relationship with their biological father.